2017
DOI: 10.33369/jeet.1.1.9-20
|View full text |Cite
|
Sign up to set email alerts
|

English Learners’ Strategies in Learning Speaking Skill (A Study of Undergraduate Student of English Education Study Progrm at Universitas Bengkulu in 2016/2017 Academic Year)

Abstract: The aim of this research was to find out the strategies used by the English Education Study Program students in learning speaking skill. It was designed as a descriptive quantitative research.  The  population  was  240  students  of  English  Education  Study  Program  of Universitas Bengkulu in the 2016/2017academic year. The samples were 60 students, taken from 25% of the total population. The data were collected by using a set of questionnai re. There  were  30  statements  of  speaking  learning  strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…The language learning strategies carried out by high students in speaking performances are cognitive, metacognitive, social, compensation, memory, and affective strategy. This finding was supported by previous finding of Trialoka et al (2017), who found that second semester college students most regularly appointed cognitive strategies. Mahdi (2018) also found that the cognitive and memorizing strategies scored were the highest averaged compared to the opposing strategies.…”
Section: Discussionsupporting
confidence: 88%
“…The language learning strategies carried out by high students in speaking performances are cognitive, metacognitive, social, compensation, memory, and affective strategy. This finding was supported by previous finding of Trialoka et al (2017), who found that second semester college students most regularly appointed cognitive strategies. Mahdi (2018) also found that the cognitive and memorizing strategies scored were the highest averaged compared to the opposing strategies.…”
Section: Discussionsupporting
confidence: 88%
“…Speaking fluently in the target language is the most crucial ability for every language learner. The extent to which the student has mastered the desired language is evidenced by his or her oral communication skills [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%